(untitled) (Eurasian Research Bulletin, 2022)
A healthy lifestyle is reflected in the physical culture, the future of the younger generation of the president, his level of physical culture, his ownership, in other words,all performances concerning the children of the nation, the country, a number of his works, manuals, brochures